Німецькомовна фольклорна бувальщина: когнітивно-дискурсивний підхід - Бучіна, Катерина Володимирівна; Buchina, K.V. (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Buchina K.V. German folk tale: a cognitive and discursive approach. — Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Humanities Sciences, Speciality 035 — Philology. — V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2020. The paper defines the German folk tale as a type of folklore discourse that constitutes a cogitative and speech interaction of a (group) author of a folklore text and its recipient/interpreter through this text. A folk tale has the following genre-productive attributes: 1) narrativity; 2) anthropocentricity; 3) appealing to supernatural phenomena; 4) mimeticity; 5) allealing to the past; 6) didacticity.
German folk tale: a cognitive and discursive approach
Німецькомовна фольклорна бувальщина розглядається як різновид фольклорного дискурсу, який становить мисленнєво-мовленнєву взаємодію колективного автора фольклорного тексту та реципієнта/ інтерпретатора за посередництвом цього тексту. Жанротвірними ознаками бувальщини є: 1) наративність; 2) антропоцентричність; 3) зверненість до надприродних феноменів; 4) міметичність; 5) зверненість до минулого; 6) дидактичність. Дискурс німецькомовної фольклорної бувальщини розглядається у трьох аспектах — когнітивному, комунікативному і мовному.
Keywords: асертив; директив; імплікатура; мовленнєвий акт; німецькомовна фольклорна бувальщина; текстовий концепт; тригер; фольклорний дискурс; assertive; directive; implicature; cognitive operation; speech act; German folk tale; stylistic device; text concept; trigger; folklore discourse